In vitro Effect of Insulin on Acanthamoeba spp - Almusawi, Sumaya A.; samir, Shaimaa A. Al; Khalid , Sundus W. (Jour Med Resh and Health Sci, 2023)
Acanthamoeba spp. is an opportunistic protozoa that causes a threat to the health of humans and animals due to its ability to develop inside and outside the host. It can cause serious and fatal infections in different places in the host's body, depending on the host's immune status and strain type. This paper aims to evaluate the lethal effect of insulin on Acanthamoeba spp. in vitro. Three concentrations (25, 50, and 100 IU/ml) were used to evaluate the lethal action of insulin at exposure periods (5, 10, and 15 minutes). The data were analyzed using SPSS and one-way ANOVA. The most potent lethal effect was recorded 15 minutes after exposure for all concentrations used, with survival rates of 44.90%, 31.90%, and 0%, respectively. Meanwhile, 5-minute exposure showed the lowest activity of 77.00%, 57.04%, and 12.00% at the concentrations used, respectively. The results of the in vitro study confirmed the effectiveness of insulin as an amoebicidal agent with increasing concentrations and exposure periods.